Deteksi Dini Masalah Emosi dan Perilaku pada Anak Usia 4 - 11 Tahun di SDN 014 Campurjo - Napisa, Napisa; Syamsidar, Syamsidar (Mando Care Jurnal, 2022)
Early age is referred to as the "critical period", because at this time basic growth will influence and determine the next child's development. At this time the development of language skills, creativity, social awareness, emotional, and intelligence runs very quickly and is the basis of subsequent developments. Moral development and the basics of personality are also formed at this time. During this critical period, useful stimulation or stimulation is needed so that its potential develops. Child development will be optimal if the interaction is cultivated according to the needs of the child at various stages of development, even since the baby is still in the womb. Emotional and behavioral problems are very common among school children, therefore it is necessary to do early detection in order to minimize emotional and behavioral problems in school-age children. The purpose of this study was to identify emotional and behavioral problems faced by children aged 4-11 years. The data collection technique used the Strength and Dificulties Questionnaire (SDQ) Questionnaire Sheet with 120 students as respondents. The results showed that emotional and behavioral problems were within normal limits of pro-social (58.33%), emotional problems (20.83%), conduct (41.66%), hyperactivity (62.5%), relationships with peers (50%). Then in the pro-social borderline (16.67%), emotional problems (20.83%), conduct (29.17%), hyperactivity (20.83%), relationships with peers (25%). And within abnormal pro-social (25%), emotional (58.34%), conduct (29.17%), hyperactivity (16.67%), relationships with peers (25%). So it can be concluded that as many as 120 respondents, children's emotional and behavioral problems are still dominant to normal. There is only 1 type of assessment on Emotion and Behavior problems which are within abnormal limits, namely on emotional  problems.